Activation of the Erector Spine Muscle with Surface Electromyography During the sit to stand to sit Transition in a Chair in Healthy Adults - Bernal Sánchez, Jose Julian; Gómez Salazar, Lessby; Wilches Luna, Esther Cecilia (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2025)
Purpose: The aim of this study was to characterize regional contraction of the erector spinae muscle (ESM) (lumbar, thoracic, and cervical) during the sit-to-stand-to-sit (STSTS) transition using surface electromyography. Methodology: A descriptive observational cross-sectional study was conducted with forty healthy young adult volunteers (20 men and 20 women) aged between 18 and 24 years. Measurements included height, weight, BMI, contraction time (seconds), and simultaneous electromyography variables: peak, mean, minimum contraction (µV), and maximum voluntary contraction during the gesture (%MVCg) in the three regions of the ESM (cervical, thoracic, and lumbar) during the STSTS transition. Qualitative and quantitative analysis of the electromyography signals was performed. Results: Participants’ age averaged 21.05±3.44 years, with 20 (50%) being female. BMI averaged 22.54±1.9. This study identified a similar ESM contraction pattern during the sit-to-stand transition in 57.5% (n=23) and during the stand-to-sit transition in 60% (n=24). Another finding was the heterogeneity of ESM activation patterns in 42.5% (n=17) during the sit-to-stand transition and 40% (n=16) in the stand-to-sit transition. Quantitative analysis revealed specific contractile differences for each region of the ESM in both amplitude and contraction times during STSTS transitions. Conclusion: This study provides valuable insights into the analysis of functional movement, segmental contraction of the ESM, and understanding of STSTS transitions in healthy individuals.